Targeted removal of epigenetic barriers during transcriptional reprogramming - Baumann, Valentin; Wiesbeck, Maximilian; Breunig, Christopher T.; Braun, Julia M.; Köferle, Anna; Ninkovic, Jovica; Götz, Magdalena; Stricker, Stefan H. (Nature communications, 2019)
Master transcription factors have the ability to direct and reverse cellular identities, and consequently their genes must be subject to particular transcriptional control. However, it is unclear which molecular processes are responsible for impeding their activation and safeguarding cellular identities. Here we show that the targeting of dCas9-VP64 to the promoter of the master transcription factor Sox1 results in strong transcript and protein up-regulation in neural progenitor cells (NPCs). This gene activation restores lost neuronal differentiation potential, which substantiates the role of Sox1 as a master transcription factor. However, despite efficient transactivator binding, major proportions of progenitor cells are unresponsive to the transactivating stimulus. By combining the transactivation domain with epigenome editing we find that among a series of euchromatic processes, the removal of DNA methylation (by dCas9-Tet1) has the highest potential to increase the proportion of cells activating foreign master transcription factors and thus breaking down cell identity barriers. Master transcription factors dominantly direct cell fate and barriers ensuring their tissue specific silencing are not clearly defined. Here, the authors demonstrate that inefficient targeted transactivation of Sox1 in neural progenitor cells is surmountable through targeted promoter demethylation using dCas9-Tet1.